A inclusão dentro da inclusão: o aluno negro e surdo na rede de educação pública da cidade de São Paulo - Sousa, Lourdes Benedita da Silva (2023)
This research addresses themes related to discrimination against individuals who are Black and disabled, people who suffer daily in our society. As we discuss inclusion, the present study is based on current legislation that prohibits and considers any form of discrimination a crime. However, despite the existence of these laws, there is a call for the creation of public policies and state intervention to guarantee essential rights for all Brazilians and more specifically, the intersectionality of black/disabled groups. Beyond social issues, the problems faced by black individuals with disabilities also have a significant impact on access and participation in the classroom. Conversely, rates of illiteracy and academic failure are increasingly pronounced within this specific group. A school is needed that rethinks the development of practices and strategies that enable freedom, access, permanence, and the right to learn that are inherent to all students. This way, social justice can be present in an equitable manner.